Family Stress and the Intergenerational Correlation in Self-Control - Deborah A. Cobb-Clark; Haniene Tayeb (Institute of Labor Economics (IZA), 2024)
We examine the correlation in self-control between parents and their young-adult children. Analyzing two decades of population-representative panel data, we exploit variation in the family environment during childhood to investigate how family stress related to: i) parenting responsibilities; ii) parents' relationship quality; iii) household finances; and iv) poor mental health shapes the transmission of self-control across generations. A finite mixture model is used to account for unobserved heterogeneity in young adults' capacity for self-control. Our results indicate that some young people may be particularly sensitive to growing up in a stressful environment, opening the door for family stress to shape the intergenerational transmission of disadvantage through the formation of self-control.
Keywords: D91; D10; J13; 330; intergenerational self-control; Brief Self-Control Scale; finite mixture models